Criminalization Of Santet In The Reform Of The Criminal Law - Setyawan, Vincentius Patria; Widiartana, Gregorius (Res Judicata, 2023)
The crime of santet is a new crime in Law Number 1 of 2023 concerning the Criminal Code. Before this article was finally included in the new Criminal Code, there was debate related to the criminalization of santet in the Criminal Code, which is related to the proof of the crime of santet related to the workings of santet and the consequences of santet in the form of non-medical illnesses. This article was written using a normative legal research method with a conceptual and statutory approach. The results of this study are that the offense of santet is a formal offense, the act that is criminalized as santet is related to someone who offers santet services and is not related to proving the workings of santet and the consequences suffered by the victim of santet.